How adults with acquired brain damage perceive computer training as a rehabilitation tool: a focus-group study. - Eriksson M; Dahlin-Ivanoff S (Scandinavian Journal of Occupational Therapy, 2002)
The aim of this study was to explore and describe how adult outpatients with acquired brain damage and referred to occupational therapy perceive computer training with the RehaCom programs, in order to evaluate the method of treatment as a tool in the rehabilitation of persons with cognitive disorders. By using focus-group discussions as a qualitative method of research when analysing the result, five themes with corresponding categories emerged, describing a development of understanding and learning about capacities. Themes describing how the participants could apply strategies to overcome shortcomings in daily occupations and the therapeutic role of the occupational therapist were identified as well. The result shows that a computer training program such as RehaCom can be used as an educational tool, for example, to guide a person who is trying to adopt compensatory strategies to avoid overload by taking pauses. It was found that anything the participants learned was also applicable to occupational performance in daily life.